Gut Bacteriophage: Current Understanding and Challenges - Sutton, Thomas D. S.; Hill, Colin (Frontiers in Endocrinology, 2019)
The gut microbiome is widely accepted to have a significant impact on human health yet, despite years of research on this complex ecosystem, the contributions of different forces driving microbial population structure remain to be fully elucidated. The viral component of the human gut microbiome is dominated by bacteriophage, which are known to play crucial roles in shaping microbial composition, driving bacterial diversity, and facilitating horizontal gene transfer. Bacteriophage are also one of the most poorly understood components of the human gut microbiome, with the vast majority of viral sequences sharing little to no homology to reference databases. If we are to understand the dynamics of bacteriophage populations, their interaction with the human microbiome and ultimately their influence on human health, we will depend heavily on sequence based approaches and in silico tools. This is complicated by the fact that, as with any research field in its infancy, methods of analyses vary and this can impede our ability to compare the outputs of different studies. Here, we discuss the major findings to date regarding the human virome and reflect on our current understanding of how gut bacteriophage shape the microbiome. We consider whether or not the virome field is built on unstable foundations and if so, how can we provide a solid basis for future experimentation. The virome is a challenging yet crucial piece of the human microbiome puzzle. In order to develop our understanding, we will discuss the need to underpin future studies with robust research methods and suggest some solutions to existing challenges.